Perancangan Sistem Order Penerbitan Iklan Pada Harian Sumut Pos Medan - Dody Hidayat; Ramli (Universitas Harapan Medan, 2025)
This study aims to design an advertising order publishing system at Harian Sumut Pos Medan, which was previously carried out manually. The existing system causes several problems, such as delays in data processing, risk of data loss, and lack of efficiency in recording and retrieving data. The research method used includes observation, interviews, and documentation studies to obtain accurate data regarding the current system. The result of this study is a desktop-based information system design using Visual Basic and MySQL database that is capable of managing advertisement order data, advertisement types, publishing schedules, and payment data in an integrated manner. The designed system improves speed, accuracy, and efficiency in data processing and report generation. This system is expected to assist Harian Sumut Pos Medan in improving the performance of advertisement order management to become more effective, efficient, and computerized.